2015
DOI: 10.5539/ijef.v7n6p126
|View full text |Cite
|
Sign up to set email alerts
|

Driving Forces of Remittance Inflow in Bangladesh: An Empirical Study

Abstract: This paper empirically investigates the major driving forces of remittance inflow in Bangladesh. Using annual data over the period from 1977 to 2011 the paper concludes that gross domestic products of host country and domestic country, exchange rate, petroleum price and skill of labour significantly influence remittance inflow in Bangladesh. One finding of the research is that skilled labour force rather sends smaller amount of remittance to the home country than the unskilled labour. This is due to the fact t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…The standard approach to check the stationary of a time series is unit root test. Among the various tests, the Augmented Dickey-Fuller (ADF) test is used widely(Adenutsi, 2010), (Islam & Nasrin, 2015). Augmented Dickey-Fuller (ADF) unit root test has been used to check whether the variables are stationary or not.…”
Section: The Augmented Dickey-fuller (Adf) Unit Root Testmentioning
confidence: 99%
“…The standard approach to check the stationary of a time series is unit root test. Among the various tests, the Augmented Dickey-Fuller (ADF) test is used widely(Adenutsi, 2010), (Islam & Nasrin, 2015). Augmented Dickey-Fuller (ADF) unit root test has been used to check whether the variables are stationary or not.…”
Section: The Augmented Dickey-fuller (Adf) Unit Root Testmentioning
confidence: 99%
“…Because of the increase in crude oil price, major host countries need more labor for gearing up the development activities which are financed by the surplus oil revenues. The finding supports (Asatryan et al, 2017;Islam & Nasrin, 2015;Naufal & Termos, 2009;Umair & Waheed, 2017).…”
Section: Analysis and Findingssupporting
confidence: 71%
“…Naufal and Termos (2009) explored that middle-eastern countries' major revenues depend on oil business and any change in the crude oil price will affect in the remittance outflows where oil price elasticity to remittances is 40. Islam and Nasrin (2015) analyzed the driving forces of remittance inflows in Bangladesh by considering the period of 1977-2011. They found that GDP of host country, GDP of home country, exchange rate, petroleum price, and skill of labor have significant impact on remittance inflow in Bangladesh.…”
Section: Oil Pricementioning
confidence: 99%
“…For instance, economic growth leads to skilled labor through education. And the skilled labor force, if migrate, can send more remittances than unskilled labor (Islam & Nasrin, 2015). Identifying the direction of causality is important for policy intervention for economic growth and remittance.…”
Section: Panel Causality Testsmentioning
confidence: 99%